Pemberdayaan Penyandang Disabilitas dalam Proses Pembangunan di Indonesia di Tinjau dari Perspektif Perundang-undangan - Ari Widiarti; Henny Rahayu Handayani (Program Studi Hukum Universitas Pamulang, 2020)
The enactment of Law Number 8 of 2016 concerning Persons with Disabilities has been going on for four years, but the involvement of persons with disabilities in community life and the development process in Indonesia has not been optimal. In general, development is a continuous process of change towards a better state based on certain principles. The failure to involve persons with disabilities in the development process stems from the stigma of society and the government towards persons with disabilities. Lack of socialization of understanding regarding equality of rights and legal protection for the community, resulting in a lot of stigma from the general public towards persons with disabilities, which results in persons with disabilities being unable to participate in the development process. The government should provide access to Persons with Disabilities in order to channel their aspirations and participate in the development process.